Microscopic description of neutron-induced fission with the Constrained Molecular Dynamics (CoMD) Model: Recent progress - Papadimitriou, S.; Souliotis, G. A.; Veselsky, M.; Bonasera, A. (HNPS Advances in Nuclear Physics, 2019)
N/A